PERTANGGUNGJAWABAN KANADA ATAS POLUSI UDARA DI KOTA NEW YORK BARDASARKAN CONVENTION ON LONG-RANGE TRANSBOUNDARY AIR POLLUTION 1979: Canada’s Responsibility for Air Pollution in New York City Under the Convention on Long-Range Transboundary Air Pollution 1979 - Eugine Vine Okteriani; Amalia Zuhra (Faculty of Law, Universitas Trisakti, 2025)
Forest fires have become an annual disaster that continues to occur in various parts of the world. The 2023 forest fires in Canada were considered severe. The 2023 wildfire season in Canada was extraordinary, with more than 5,700 fire incidents having burned 13.7 million hectares by August 16, 2023, since the start of the fire season. The identified issue is whether Canada should be held responsible for air pollution in New York under the 1979 Convention on Long-Range Transboundary Air Pollution (CLRTAP) and whether the measures taken by Canada to address air pollution in New York have been in accordance with the provisions of the 1979 CLRTAP. The method employed is normative legal research, a descriptive-analytical approach that utilizes secondary data, incorporates qualitative data analysis, and employs deductive reasoning. The results of the study indicate that Canada should be held responsible for the air pollution in New York City, as Canada has fulfilled the elements of state responsibility as stipulated by the 1979 CLRTAP, and that Canada’s measures have complied with the convention through international cooperation.